Voices of SARDO Students: A Phenomenological Study on the Impact of Learning Activity Sheets in Enhancing Filipino Language Proficiency - Gavileño, Analyn; Besa, Dayanara (International Journal of Arts, Sciences and Education, 2025)
This study aims to assess the effectiveness of Learning Activity Sheets (LAS) in the learning process of Students-at-Risk of Dropping Out (SARDO) in Filipino. Guided by Transcendental Phenomenology, this research explores the lived experiences, perspectives, and challenges in using LAS as an alternative instructional material. Twelve SARDO students from Tacurong National High School participated in the study, where in-depth interviews were conducted to examine their insights. Findings reveal that LAS provides a structured learning guide and helps improve reading comprehension and text analysis skills. However, students encountered challenges such as limited vocabulary, difficulty in following instructions, and a lack of immediate teacher support. Despite these obstacles, they recognized the LAS as a valuable learning tool. The study recommends enhancing the design of LAS to make it more effective, interactive, and responsive to the needs of SARDO students. This research contributes significantly to the development of more inclusive instructional materials that can help improve the learning outcomes of students with specialized educational needs.